Tamoxifen inhibits cell proliferation by impaired glucose metabolism in gallbladder cancer. Issue 2 (28th November 2019) - Huang, Shuai; Wang, Hui; Chen, Wei; Zhan, Ming; Xu, Sunwang; Huang, Xince; Lin, Ruirong; Shen, Hui; Wang, Jian
Abstract: Gallbladder cancer (GBC) is the leading malignancy of biliary system showing refractory chemoresistance to current first‐line drugs. Growing epidemiological evidences have established that the incidence of GBC exhibits significant gender predominance with females two‐threefold higher than males, suggesting oestrogen/oestrogen receptors (ERs) signalling might be a critical driver of tumorigenesis in gallbladder. This study aims to evaluate the antitumour activity of tamoxifen (TAM), a major agent of hormonal therapy for breast cancer, in preclinical GBC model. Quantitative real‐time PCR was used to investigate mRNA levels. Protein expression was measured by immunohistochemistry and Western blot. Glycolytic levels were measured by glucose consumption and lactic acid measurement. The antitumour activity of TAM alone or with cisplatin was examined with CCK8 assay, colony formation, flow cytometry and in vivo models. The results revealed that ERɑ expression was higher in GBC tissues and predicted poor clinical outcomes. TAM was showed effective against a variety of GBC cell lines. Mechanical investigations revealed that TAM enabled potent reactive oxygen species (ROS) production by reduced nuclear factor Nrf2 expression and its target genes, leading to the activation of AMPK, which subsequently induced impaired glycolysis and survival advantages. Notably, TAM was demonstrated to sensitize GBC cells to cisplatin (CDDP) both in vitro and in vivo. In agreement with these findings, elimination of oestrogens by ovariectomy in nude mice prevented CDDP resistance. In summary, these results provide basis for TAM treatment for GBC and shed novel light on the potential application of endocrine therapy for patients with GBC.